Pengembangan Keterampilan Manajemen Keuangan dan Digitalisasi Pemasaran pada UMKM Assyafa Batik Lampung - Rendi Saputra; Ritali Evi Mudrikah; Melisa Purnama; Rizki Pebriansyah; Sofie Dea Aulia (Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to assist the Assayafa Batik Lampung MSME in Bandar Lampung City in improving financial management and digital marketing skills. The partner faced several challenges, including poorly organized financial records, the mixing of personal and business finances, and the use of conventional promotional methods. The program was implemented through training, mentoring, and hands-on practice in proper financial recording based on accounting principles, as well as the utilization of digital media for product promotion. The results showed an increase in participants’ knowledge and skills in financial management and their ability to use online platforms to expand market reach. Overall, this program contributes to strengthening the digital capacity and enhancing the competitiveness of MSMEs in the current era of digital transformation.